Pengaruh Halal Awareness, Promosi dan Kualitas Layanan Terhadap Keputusan Penggunaan Fitur Food Delivery di Aplikasi Ojek Online Pada Masyarakat Muslim di Jawa Timur - Ardana, Rezalistia; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2024)
This study aims to determine the effect of halal awareness, promotion and service quality in the decision to use food delivery services in online motorcycle taxi applications by Muslim communities in East Java. This research method uses a quantitative approach with primary data collection through a google form questionnaire which is then distributed. Sampling using purposive sampling method which has the criteria of the East Java Muslim community and has used online motorcycle taxi food delivery (Go-food, Grabfood, Maxim Food and others). The research findings show that halal awareness does not have a positive and significant effect on the decision to use the food delivery feature in the online motorcycle taxi application. Promotion variables and service quality show that there is a positive and significant influence on the decision to use the food delivery feature in online motorcycle taxi applications for Muslim communities in East Java. Thus, the application of halal awareness in Muslim communities in East Java in the decision to use food delivery in online motorcycle taxi applications is still low and not optimal because Muslim communities have various backgrounds that can shape consumption patterns while promotions can make a source of motivation in purchasing using online motorcycle taxi applications and the quality of service of online motorcycle taxi applications is in accordance with consumer expectations during transactions.